Which is the right dose of EU cohesion policy for economic growth? - Hagen, Tobias; Mohl, Philipp (Mannheim, 2008)
"The current empirical literature on the impact of EU Cohesion Policy on the economic growth rates of the European regions mainly relies on functional form assumptions. However, it is ex ante not clear which functional form is appropriate with regard to the relationship between structural funds payments and regional economic growth. In order to avoid such assumptions, this paper applies the method of generalized propensity score (GPS) to a sample of 122 NUTS-1 and NUTS-2 EU-15 regions for the time period 1995-2005, which leads to the estimation of a dose-response function, as proposed by Hirano and Imbens (2004). Our results indicate that structural funds payments have a positive, but not statistically significant, impact on the regions' average three-year growth rates. This implies that it does not matter which "dose" of structural funds payments a region receives. "